INTERNALIZATION OF PANCASILA VALUES IN PANCASILA AND CIVIC EDUCATION LEARNING IN THE ATTEMPT OF BRINGING THE MULTICULTURAL EDUCATION INTO REALITY - Sutoyo, Asrowi, Muhammad Ahyar & Sri Anitah (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Indonesia is a pluralistic nation. Indonesian plurality can be seen fromhorizontal and vertical perspective. Indonesian plurality brings both positiveand negative effects. The positive effect of plurality is that this nation can bea great and strong nation. However, if this plurality is not managed well,friction and conflict and even nation dissension will result. Amid science andtechnology advance, as a plural nation, Indonesia needs an education that canbuild this nation into a developed and great nation, but with character anddignity based on the unity. Education that can answer this challenge ismulticultural education. One alternative of multicultural education is theinternalization of Pancasila values into Pancasila and Civic Education (PPkn)learning. The internalization of Pancasila values is the process of impartingand appreciating Pancasila values manifested into the students’ attitude andbehavior. If the internalization of Pancasila values can be actually broughtinto reality, the function of Pancasila would run dully, as the state foundationand ideology. It means that all aspects of statecraft and Indonesian nation’sattitude and behavior in living within society, nation and state should bebased on Pancasila values.Keywords: Internalization of Pancasila values, Pancasila and Civic EducationLearning, Multicultural Education